Management of dermatophytosis: Real-world Indian perspective - Manjunath Shenoy; Shital Poojari; Madhu Rengasamy; Maya Vedmurthy; Shyamanta Barua; Dhiraj Dhoot; Hanmant Barkate (Wolters Kluwer Medknow Publications, 2023)
Background: In spite of the availability of multiple consensus statements on dermatophytosis management, different treatment approaches have been experienced in India and require more scrutiny to further update guidelines and improve patient care. Aim: To determine the different approaches in dermatophytosis diagnosis and management among dermatologists in India. Materials and Methods: A web-based questionnaire was created and validated by five panelists with experience of >15 years in dermatophytosis and then circulated to about 2,000 dermatologists in India in September 2021 for a real-world management scenario. Results: Out of 2,000 dermatologists, 459 responded. About half of the dermatologists (51%) routinely conduct potassium hydroxide mount (KOH) at the initiation of therapy. Similarly, about 53% of dermatologists initiate the management of dermatophytosis with combination therapy in all types of dermatophytosis for 4-6 weeks depending upon severity. Different types of combinations are being practiced, such as either two systemic and one topical, two topicals and one systemic, but the combination of one systemic and one topical (69%) is the most commonly practiced. Itraconazole (100 mg twice a day) and luliconazole are the most commonly prescribed antifungal medications. In case of non-response to routine dose of systemic anti-fungals, about 72% of dermatologists up dose them. Most of them continue these drugs for additional 1-2 weeks after clearance of the disease. Additionally, keratolytics and moisturizers are commonly prescribed. Additionally, 62% advise liver function tests (LFTs) at the initiation of therapy, whereas 72% advise monitoring adverse effects due to systemic antifungal drugs during treatment. Conclusion: Combination therapy stood out as the need of the hour in the current menace of dermatophytosis with timely monitoring of laboratory tests for adverse events due to the use of systemic antifungals for a longer duration.